2017
DOI: 10.1039/c7ta00905d
|View full text |Cite
|
Sign up to set email alerts
|

Base stable poly(diallylpiperidinium hydroxide) multiblock copolymers for anion exchange membranes

Abstract: The development of base-stable cationic groups for anion exchange membranes is important for application in alkaline fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 67 publications
2
77
0
Order By: Relevance
“…This obvious hydrophilic/hydrophobic microscopic phase separation is beneficial for the transmission of hydroxyl ions in AEMs . Compare with the previous AEMs contain aromatic backbones with the similar IEC values,,, the AEMs obtained in the present work showed a higher conductivity at the same temperature, which probably due to the aliphatic backbone chain lead to a higher water uptake and the formation of obviously microscopic phase separation structure in the AEMs.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…This obvious hydrophilic/hydrophobic microscopic phase separation is beneficial for the transmission of hydroxyl ions in AEMs . Compare with the previous AEMs contain aromatic backbones with the similar IEC values,,, the AEMs obtained in the present work showed a higher conductivity at the same temperature, which probably due to the aliphatic backbone chain lead to a higher water uptake and the formation of obviously microscopic phase separation structure in the AEMs.…”
Section: Resultssupporting
confidence: 71%
“…The excellent alkaline stability of spirocyclic QA cation was also confirmed by theoretical calculations . Based on their determination of alkaline stability of the small molecules, the aromatic polymers with pendent spirocyclic QA and piperidinium cations have been synthesized and used to prepare AEMs . Hickner's work indicated that the backbone of AEMs have effect on the alkaline stability of cations, and the AEM has aromatic backbone with ether groups is not stable in alkaline condition.…”
Section: Introductionmentioning
confidence: 86%
“…42 The high stability of the alicyclic QAs has been rationalized by a low ring strain combined with the constrained conformations imposed by the ring structure, which increase the transition state energy of both substitution and elimination reactions. 42 Later studies by us and others on AEMs functionalized with alicyclic cations such as piperidinium 25,26,44 and different spirocyclic QAs 32,37,[45][46][47][48][49][50][51] have conrmed a high alkaline stability. However, the results also indicate that the stability is highly dependent on precisely how the cations are attached to the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%
“…However, attaching those molecules into the polymer backbone is a challenge. As a result, there are currently only a few AEMs prepared using heterocyclic and spirocyclic molecules [96][97][98]. Strasser et al [96] prepared promising AEMs by copolymerizing the end-functionalized polydiallylpiperidinium oligomers with polysulfone monomers.…”
Section: Path Dmentioning
confidence: 99%